2002
DOI: 10.7202/005647ar
|View full text |Cite
|
Sign up to set email alerts
|

Les systèmes fluviaux à chenaux anastomosés en milieu périglaciaire : la Léna et ses principaux affluents (Sibérie centrale)

Abstract: Résumé Cette étude concerne les rivières à régime de débâcle en milieu périglaciaire à pergélisol épais et continu. La Léna et ses principaux affluents (Aldan, Vilioui) présentent des formes fluviales spécifiques : on distingue dans le lit mineur des chenaux larges et peu profonds, qui enserrent des bancs sableux et des îles boisées, tandis que dans la plaine et les îles se développent des bras anastomosés plus sinueux et plus étroits. L'objectif de cette étude préliminaire est la compréhension du fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
1
14
0
2
Order By: Relevance
“…Between wet and arid cold-climate conditions, a range of fluvial planforms is seen which is similar to that of warmer climates, with braided rivers predominantly in arid conditions. A study of the Lena basin rivers showed the importance of log jams and ice jams (Gautier and Costard, 2000). With the exception of bank strength, which is influenced by permafrost (see section 'Landforms and Processes'), these have no unique link to periglacial conditions.…”
Section: Morphologymentioning
confidence: 99%
“…Between wet and arid cold-climate conditions, a range of fluvial planforms is seen which is similar to that of warmer climates, with braided rivers predominantly in arid conditions. A study of the Lena basin rivers showed the importance of log jams and ice jams (Gautier and Costard, 2000). With the exception of bank strength, which is influenced by permafrost (see section 'Landforms and Processes'), these have no unique link to periglacial conditions.…”
Section: Morphologymentioning
confidence: 99%
“…The width of the channels varies between several hundred metres and three kilometres. These multiple channels enclose large forested islands from 1 to 5 km long and large sandy bars (Anisimova et al, 1973;Gautier and Costard, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thawing of the ice (for any ice content) within a porous medium reduces the strength of the thawed sediments and produces easily removable uncemented ground (Jahn, 1975). During the thawing period, with a relatively high discharge, the thawed sediments are swept away (Gautier and Costard, 2000). In this typical situation, the water flow in permanent contact with frozen river banks induces a combination of thermal and mechanical erosion.…”
Section: Introductionmentioning
confidence: 99%
“…A numerical model in combination Figure 1. Water mean temperatures and discharge in the Lena River at Tabaga (Gautier and Costard, 2000). This figure shows the instantaneous discharge against time and suggests that the majority of the discharge occurs during a short breakup period of about one month in June with a laboratory simulation is proposed to understand the strong erosion rates along some river banks.…”
Section: Fluvial Thermal Erosionmentioning
confidence: 99%
“…Their fluvial regime maximizes bed-sediment transport under very low gradient and efficient discharges. Therefore, the sediment load (mainly sandy deposits) does not migrate over long distances downstream and is accumulated on wide bars and long islands (Gautier and Costard, 2000).…”
mentioning
confidence: 99%